Karyopherins in nuclear transport of homeodomain proteins during development - Ye, Wenduo (2011)
Homeodomain proteins are crucial transcription factors for cell differentiation, cell proliferation and organ development. Interestingly, their homeodomain signature structure is important for both their DNA-binding and their nucleocytoplasmic trafficking. The accurate nucleocytoplasmic distribution of these proteins is essential for their functions. We summarize information on a) the roles of karyopherins for import and export of homeoproteins, b) the regulation of their nuclear transport during development, and c) the corresponding complexity of homeoprotein nucleocytoplasmic transport signals.